Effect of the new rural cooperative medical system on farmers’ medical service needs and utilization in Ningbo, China - Jianhua Chen; Hai Yu; Hengjin Dong (BMC Health Services Research, 2016)
Abstract Background Many countries are developing health mechanisms to pursue the goal of universal coverage. In China, a rural health insurance system entitled New Cooperative Medical System (NCMS) has being developed since 2003. This paper aims to explore the changes in the health service needs and utilization among rural residents in Ningbo, China after the implementation of the new rural cooperative medical system (NCMS), and provide evidence to further improve the strategies of NCMS in China. Methods Stratified multistage cluster sampling was used to randomly select 10 villages from 5 townships in Yuyao and Fenghua counties of Ningbo Municipality. Eighty families were selected from each village, and face-to-face interviews were conducted by trained investigators to collect data using questionnaires. Results The two-week visiting rate and prevalence of chronic diseases among the farmers included in the study was 25.40 and 22.50 %, respectively, which were higher than the levels in 2003 and 2008. The rate of not visiting the healthcare facility amongst those with illness, and the rate of non- hospitalization amongst those who required it were 32.36 and 0.60 %, respectively, which was lower than the levels in 2003 and 2008. Most of the outpatient visits were to the village clinics, while the hospitalizations were mainly to county hospitals. Conclusion NCMS greatly affected the utilization of healthcare services from outpatient clinics and improved the hospitalization rate in county hospitals. Financial difficulties are not the major causes of non-hospitalization and non-visiting any longer. These findings suggest that the NCMS policies alleviated the medical burdens of farmers in a certain degree.